Designing A Language Lesson: Pedagogical and Linguistic Perspectives - Hidayat, Didin Nuruddin (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2018)
Designing a language lesson is a challenging task for teachers. In order to have a good language lesson, teachers cannot just rely on the textbook. They need at least to develop the lesson from the textbook or even to design their own lesson. Teachers also need to consider how they are going to apply the lesson planned in the classroom. Another consideration would be to integrate the specific language skill and/or element with the other skills. This is essential in order to achieve the utmost results of teaching and learning. This paper discusses a language lesson in the area of grammar - Used To Â - designed by the author. The lesson is not only intended to expose learners with the structure and rules of grammar, but also allow learners to practice the grammar in use. Hence, the developed grammar lesson aimed to improve the communicative competence of the learners. Considering the wide aspect of teaching analysis, the present article focuses on the application of the lessons in the classroom, the aspects of language skills covered, as well as the linguistic foundation for the exercises. It is hoped that this article can provide insights to language educators in developing grammar lessons that cater to the considerations of pedagogical and linguistic perspectives.